ANNOTATED TRANSLATION OF “A CONVICT’S DAUGHTER” - Sayekti, Nurul (Universitas Gunadarma, 2017)
This is an annotated translation. The purposes of this research are to attain factual information concerning the problems faced by the researcher in the course of translating the source text and to find the solutions of the problems based on the relevant principles, strategies and theories of translation. The method used by the researcher to conduct this research are introspetive and retrospecive methods. The result of the research showed that the 4 chosen data to be analyzed used the following translation strategies: loan, calque, unit shift, and interpersonal change. The analysis of the data are based on the principles of translation and translation strategies. It is found out that not all 30 translation strategies and 13 principles of translation are used. Keywords: Translation, Annotated translation, Introspective, Retrospective